1993
DOI: 10.1177/096120339300200605
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Cytokines (TNFα and IL-6) and Acute Phase Proteins (CRP and α1AG) related to the Disease Course in Patients with Systemic Lupus Erythematosus

Abstract: Tumor necrosis factor alpha (TNF alpha) and interleukin-6 (IL-6) play a main role in inducing acute phase protein production by hepatocytes. This study describes the serum levels of TNF alpha and IL-6 in relation to serum levels of C-reactive protein (CRP) and alpha 1-acid glycoprotein (alpha 1AG) in three systemic lupus erythematosus (SLE) patients. Disease courses of these patients were divided in a total of 19 clinical periods, according to the clinical symptoms and interleukin profiles. Significantly eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 22 publications
5
37
1
Order By: Relevance
“…[15][16][17][18][19] Consistent with data from other labs, we report here that SLE patients have increased serum TNF-a levels. [43][44][45] TNF-a, a common marker for the activation status of macrophages and DCs, is primarily secreted by activated monocytes/macrophages and may induce the increased expression of Tim-4, thus promoting Th2 cell proliferation via interaction with Tim-1.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[15][16][17][18][19] Consistent with data from other labs, we report here that SLE patients have increased serum TNF-a levels. [43][44][45] TNF-a, a common marker for the activation status of macrophages and DCs, is primarily secreted by activated monocytes/macrophages and may induce the increased expression of Tim-4, thus promoting Th2 cell proliferation via interaction with Tim-1.…”
Section: Discussionsupporting
confidence: 86%
“…These results indicate that TNF-a plays an important role in the development of SLE, which is consistent with data from other labs. 16,17 We also found a positive correlation between Tim-4 mRNA levels in PBMCs and TNF-a concentrations in serum in SLE patients (P,0.05, r50.4204) (Figure 3b). …”
Section: Positive Correlation Of Tim-4 Mrna In Pbmcs With Serum Tnf-amentioning
confidence: 62%
See 1 more Smart Citation
“…These data could not be explained by changes in disease course or therapy influences. It was concluded that other factors (other than TNF-α and IL-6) may play a role in the regulatory pathway of the APR in SLE (Meijer, Huysen et al 1993). …”
Section: Possible Mechanisms Of Low Apr Responsementioning
confidence: 99%
“…Serum levels of pro-inflammatory cytokines such as IL-1, IL-6, and TNF␣ have been found to correlate with SLE disease activity in most studies, [1][2][3][4][5][6] suggesting that they may represent a driving force behind disease progression or pathology. In addition, certain studies have demonstrated increased production of these cytokines by peripheral blood mononuclear cell cultures spontaneously or after stimulation, suggesting that cells from these patients may have a generalized increased capacity for the production of pro-inflammatory cytokines.…”
mentioning
confidence: 99%